ANALYSIS OF OPPORTUNITIES AND CHALLENGES IN TRADE OF WHEAT AGRICULTURAL PRODUCTS (CASE STUDY ON TRADE BETWEEN INDONESIA AND THE RUSSIAN FEDERATION) - Amalia, Dinda Friska; Daspar, Daspar (Universitas Islam Malang, 2025)
Wheat is a strategic commodity that is critical to Indonesia's food security and food processing industry. Indonesia maintains significant trade relations with various supplier countries, including the Russian Federation, as the country is largely dependent on wheat imports. Using trends and data from the past five years, this article investigates the prospects and barriers in wheat trade between Indonesia and Russia. The study uses information from the Central Bureau of Statistics (BPS), the Food and Agriculture Organization (FAO), the Ministry of Agriculture (MOA), the World Trade Committee (UNCTAD), and the International Double Committee (IGC). This analysis shows that while there are great opportunities to increase the volume of Russian wheat imports to Indonesia and bilateral cooperation opportunities, Russia's export protection policies, global price fluctuations, and geopolitical dynamics are the main issues affecting the stability of Indonesia's wheat supply. To maximize Indonesia's benefits from wheat trade, this article suggests ways to diversify import sources, improve supply chain efficiency, and enhance bilateral trade cooperation